You are on page 1of 43

1

(Matrix and Determinants)

(matrix) (function)
(row) (column)
(element)

[ ] ( )
A , B , C , ..
a, b, c,
m n
m x n m n
1

A m x n ai j
A [ ]

a11
a21
.
.
am1


A = [ a ij] m x n

a11
a12
a21
a22

a12
a22
.
.
am2

a13
a23
.
.
am3

i = 1, 2, 3, m
j = 1, 2, 3, n

..
..
..
..
.

A
A
A
A

a1m
a2n
.
.
amn

mn

1 1
1 2
2 1
2 2



(Addition and Subtraction of matrix)
2

A = [ aij ] mxn , B = [ bij ] mxn

1. A B A B
A + B = [ aij + bij ] mxn i = 1, 2, 3, .m
j = 1, 2, 3, ..n
2. A B A
B A - B = [ aij - bij ] mxn i = 1, 2, 3, .m
j = 1, 2, 3, ..n

2 4 3
A = 0 1 2
-1 5 2

,B =

2 -1 1
4 3 2
1 2 4

1. A + B
2. A - B
3. A + B - C

1) A + B

2+2 4+(-1) 3+1


0+4 1+3
2+2
-1+1 5+2
2+4
4
4

3
4

4
4

1 2 3
, C= 0 1 4
2 1 0

2) A - B

0
2-2
0-4
-1-1

7
4-(-1)
1-3
5-2

6
3-1
2-2
2-4

0
-4
-2

5
-2
3

2
0
-2

3) A + B - C =

2+2-1
0+4-0
-1+1-2

3
4
-2

4+(-1)-2
1+3-1
5+2-1
1
3
6

3+1-3
2+2-4
2+4-0

1
0
6


(scalar)


A = [ aij ] mxn A = [ aij ]
i = 1, 2, 3, .m
j = 1, 2, 3, ..n

1 2 -1
A = 3 7 -5
4 6 8
2A , -3A , A

1) 2A =

2(1)
2(3)
2(4)

2(2)
2(7)
2(6)

2(-1)
2(-5)
2(8)

2) -3A =

(-3)(1) (-3)(2) (-3)(-1)


(-3)(3) (-3)(7) (-3)(-5)
(-3)(4) (-3)(6) (-3)(8)

3) A =

(1)
(3)
(4)

(2) (-1)
(7) (-5)
(6) (8)

2 4 -2
6 14 -10
8 12 16

-3 -6 3
-9 -21 15
-12 -18 -24

1 -
3/2 7/2 -5/2
2 3 4

2 4 3
A = 0 1 2
-1 5 2
1) 2A + 3B
2) A C

,B =

2 -1 1
4 3 2
1 1 1

1 2 3
, C= 0 1 4
2 1 0

1) 2A + 3B

= 2

2 4 3
0 1 2
-1 5 2

2(2) 2(4)
2(0) 2(1)
2(-1) 2(5)

4 8 6
0 2 4
-2 10 4

+3

2(3)
2(2)
2(2)

2 -1 1
4 3 2
1 1 1
3(2) 3(-1) 3(1)
+ 3(4) 3(3) 3(2)
3(1) 3(1) 3(1)
6 -3 3
12 9 6
3 3 3

10 5 9
= 12 11 10
1 13 7

2) A C

2 4 3
0 1 2
-1 5 2
2
0
-1

4
1
5

1 2 3
0 1 4
2 1 0
3
2
2

2 4 3
0 1 2
-1 5 2

(1) (2) (3)


(0) (1) (4)
(2) (1) (0)

1 3/2
1 3 3/2
0 2 = 0 0
1 0
-2 -4 2

(Multiplication of Matrix)





A
B

A2x3

B3x2

2x3
3x2

= AB2x2

A B
AB 2x2

6

A
B

A2x2

2x2
3x2

B3x2

A mxp B pxn
A B AB mxn cij
i A j B

A = [ aij ] mxp , B = [ bij ] pxn AB = C = [ cij ]

mxn

cij = [ ai1 b1j + ai2 b2j + ai3 b3j +..+ aip bpj ]
p

= aik bkj

i = 1, 2, .m

k 1

j = 1, 2, ..n

AB = C

a11 a12 a13 . a1p


a21 a22 a23 . a2p

b11 b12 b13 . B1j . b1n


b21 b22 b23 . b2j . b2n

ai1 ai2 ai3 . aij


.
. .
.
am1 am2 am3 . amp

bi1 bi2 bi3 . bij . b3n


. . .
.
.
bp1 bp2 bp3 . bpj . bpn

c11 c12 . cij . c1n


c21 c22 . c2 j. c2n
=

ci1 ci2 . cij . cin


. . . .
.
cm1 cm2 . cmj . cmn

cij = [ai1 ai2 . aij . aip]

b1j
b2j
.
bij
.
bpj

= ai1 b1j + ai2 b2j .. + bip bpj

cij AB = [ i A ] x j
B
= I A j
B
4

2 4 3
A = 0 1 2
-1 5 2
1) AB

,B =

2) BA

2 -1 1
4 3 2
1 1 1
3) (AB)C

1 2 3
, C= 0 1 4
2 1 0
4) A(BC)

8
2
0
-1

AB =

4
1
5

3
2
2

2
4
1

1 x 1
2 x 1
3 x 1

(2)2 + (4)4 + (3)1


(0)2 + (1)4 + (2)1
(-1)2 + (5)4 + (2)1

4 + 16 + 3
(-2) + 12 + 3
0+4+2
0+3+2
(-2) + 20 + 2 1 + 15 + 2

23
6
20

2 -1
4 3
1 1

13
5
18

-1
3
1

1
2
1

1 x 2
2 x 2
3 x 2

1 x 3
2 x 3
3 x 3

(2)(-1) + (4)3 + (3)1 (2)1 + (4)2 + (3)1


(0)(-1) + (1)3 + (2)1 (0)1 + (1)2 + ( 2)1
(-1)(-1) + (5)3 + (2)1 (-1)1 + (5)2 + (2)1

2+8+3
0+2+2
(-1) + 10 + 2

13
4
11

2
BA

1
2
1

2
0
-1

(2)2 + (-1)0 + (1)-1)


(4)2 + (3)0 + (2)(-1)
(1)2 + (1)0 + (1)(-1)

4
1
5

3
2
2

(2)4 + (-1)1 + (1)5


(4)(-1) + (3)1 + (2)5
(1)4 + (1)1 + (1)5

(2)3 + (-1)2 + (1)2


(4)3 + (3)2 + (2)2
(1)3 + (1)2 + (1)+2

9
=

4 + 0 + (-1)
6 + 0 + (-2)
2 + 0 + (-1)
3
12
4
29
1
10

8 + (-1) + 5
16 + 3 +10
4+1+5
6
22
7

6 + (-2) + 2
12 + 6 +4
3+2+2

3
AB 1

(AB)C

23 13 13
6
5 4
20 18 1 1

1
0
2

2
1
1

3
4
0

(23)1 + (13)0 + (13)2 (23)2 + (13)1 + (13)1 (23)3 + (13)4 + (13)0


(6)1 + (5)0 + (4)2
(6)2 + (5)1 + (4)1
(6)3 + (5)4 + (4)0
(20)1 + (18)0 + (11)2 (20)2 + (18)1 + (11)1 (20)3 + (18)4 + (11)0

(AB) C =

49
14
42

72
21
69

121
38
132

A (BC)

BC
2
= 0
-1

4 3
1 2
5 2

(2)4 + (4)8 + (3)3

4
8
3

4
13
4

2
24
7

(2)4 + (4)13 + (3)4

(2)2 + (4)24 + (3)7

10
=

(0)4 (1)8 + (2)3


(-1)4 (5)8 + (2)3
49
14
42

A(BC) =

72
21
69

(0)4 + (1)13 + (2)4


(-1)4 + (5)13 + (2)4

(0)2 (1)24 + (2)7


(-1)2 (5)24 + (2)7

2 -1 1
4 3 2
1 1 1

1
0
2

121
38
132

2
A = 0
-1

4
1
5

3
2
2

, B =

2
0
-1

4
1
5

3
2
2

2
4
1

4
0
3

,C =

1) (A + B) C
2) AC + BC

1
(A + B)

(A+B)C =

4
0

4 + 0 +8
4+0+8
0+0+6

12
12
6

15
16
9

+
1
1

1
2
1

4
2

8+3+4
8+4+4
0+6+3
24
28
24

-1
3
1

12 + 12 + 0
12 + 16 + 0
0 + 24 + 0

4 3 4
4 4 4
0 6 3

2
1
1

3
4
0

11
2
AC + BC

2 4 3
0 1 2
-1 5 2

2+0+6 4+4+3 6+16+0


2+0+2 4+(-1)+1 6+(-4)+0
0+0+4 0+1+2 0+4+0 + 4+0+4 8+3+2 12+12+0
(-1)+0+4 (-2)+5+2 (-3)+20-0
1+0+2 2+1+1 3+4+0

8 11
4 3
3 5

12
12
6

15
16
9

1 2 3
0 1 4
2 1 0

22
4
17

2 -1
+ 4 3
1 1

1
2
1

1
0
2

2 3
1 4
1 0

4 4 2
8 13 24
3 4 7

24
28
24

A = [ aij ] mxn , B = [ bij ] mxn


A = B aij = bij i = 1, 2, 3, .m
j = 1, 2, 3, ..n

12

a11 a12 . a1n
a21 a22 . a2n
A=

. . . .
am1 am2 . amp

b11
b21
,B = .
.
bm1

a11 =b11 , a12 = b12 ,

b12 . b1n
b22 . b2n
. . .
. . .
bm2 . Bmn

a13 = b13 , . , amn = bmn

2x
4

8
y

x , y

2x = 8
4 =y

x
-5

4
y

x , y

x = 1
y = 4

1 4
-5 4

x = 8/2 = 4

13

-5 8 7
3 2x -2
4 1 -1

-3 4 0
1 2 -1
-5 1 -y

-3
1
-5

-12 3 48
-3 2 -12
3z 17 -9

x, y, z

x
3

2x

-2

= c21 = -3 [ c21 2
1
]

-9 + 2x + 10 = -3
2x = -4
x = -2
y
4

-1

0
-1
-y

= -9 = c33

4(0) + (1) (-1) + (-1) (-y) = 9


-1 + y = -9
y = -9+1 = -8
z
4

-1

-3
1
-5

4(-3) + (1) (1) + (-1) (-5) =

= 3z = c31

3z

14
-12 + 1 + 5 = 3z
-6 = 3z
= -2 = z
x = -2 , y = -8 , z = -2

1) A(BC) = (AB)C
2) A(B+C) = AB + AC
3) (A+B)C = AC + BC
4) (AB) = (A) B = A(B)
5) A =
6)
AB BA
7) AB = A B
8) A = B AC = BC CA = CB AC CA
BC CB
9) AB = AC B = C

6
(Transpose of Matrix)
A A At A
A transpose At A

A = [ aij ] mxn At = [ aij ] nxm

15

i = 1, 2, 3, .m
j = 1, 2, 3, ..n

9
A = 1
4

At =

At

2 3
5 6
1
2
3

4
5
6


A , B , C K

1. (At)t = A
2. (KA) t = KA t
3. (A + B) t = A t + B t
(A + B + C) t = A t + B t + C t
4. (AB) t = B t A t
(ABC) t = C t B t A t

10
A =

(Symmetric matrix)
B B + B t

1 4
-5 4

16
A =

1 4
-5 4

A = At
A

11
1 2
4 3
-1 2

A =

1
7
4

A
A + At

1 2 1
4 3 7
-1 2 4

A , At AAt AtA

(Triangular matrix)
(main diagonal)

1 4 -1
2 3 2
1 7 4

2 6 0
6 6 9
0 9 8

1 0
5 2

1 0
0 3

1 2 3
0 4 0
0 0 7

1 0 0
4 5 0
6 7 8

17
(Echelon matrix) A mxn
(Echelon matrix)

1. 0 1

2. 0 1 ()

12
1)

1 4
0 1

echelon matrix

2.

1 5 7
0 1 4
0 0 1

echelon matrix

3.

1
0
0
0

2
1
0
0

3
5
1
0

4
6
7
1

echelon matrix

4.

0
0
0
0

1
5
0
0

4
6
1
0

9
9
4
1

2 1

18
5.

1 9 0
0 0 1
0 1 7

1 2
3

10
(Idempotent matrix)
Idempotet matrix A2 = A

A3 = A , A4 = A , An = A

11

A A1 = A n
An = A.A.A.A (n ) (Am) (An) = Am+n
(Am)n = Amn (ABm) = Am Bm

A5 = A2+3
A6 = (A2)3
(AB)3 = A3B3

, B4 = (B2) (B2)

(The determinant of matrix)




A det A |A|

1. 1x1
A = [a11] det(A) = a11
A = [5] det A = 5
2. 2x2

19
A =

a11 a12
a21 a22

det A = |A| = a11


a21

a12
a22

= a11 a22 - a21a12


12

A =

2 5
7 10

det A

+
det A =

2
7

5
10

= (2) (10) - (7) (5)


= 20 35
= -15
13

A =

-1 -3
-5 -4

det A

det A =

-1

-3

20
-5

-4

= (-1) (-4) - (-5) (-3)


= 4 15
= -11
14

A =

4 -5
3 -10

det A

det A =

4
3

-5
-10

= (4) (-10) - (3) (-5)


= -40 + 15
= -25

3. 3x3
3x3 1, 2

3

a11 a12 a13
A = a21 a22 a23
a31 a32 a33
+ +
+
a11 a12 a13 a11 a12

21
det A = |A| =

a21
a31

a22 a23 a21 a22


a32 a33 a31 a23

= a11a22a33 + a12a23a31 + a13a21a23 a31a22a13 a32a23a11 a33a21a12

15

A =

1 2 3
1 3 5
1 5 11

det A

det A =

=
=
=

1 2 3 1 2
1 3 5 1 3
1 5 12 1 5
+
+ +
(1)(3)(12) + (2)(5)(1) + (3)(.1)(5) - (1)(3)(3) - (5)(5)(1) (12)(1)(2)
36 + 10 + 15 - 9 25 - 24
3

4. 3x3
3x3 2x2 3x3

A = [aij]nxn A
( )
(cofactor) ( )

22
a11 a12 a13 . a1n
a21 a22 a23 . a2n

A =

.
. .
.
an1 an2 an3 . ann
1
det A = a11 C11 + a12 C13 + a13 C13 + . ,+ a1n C1n
2
det A = a21C21 + a22 C22 + a23 C23 + . ,+ a2n C2n
i
det A = ai1Ci1 + ai2Ci2 + . + ainCin
=

aij Cij
j 1

1
det A = a11C11 + a21 C21 + . , +an1 Cn1
Cij = (-1)i+j M ij aij M ij
i j

16

A =

1 2 4
3 6 1

23
0 1 1
2 (a11 = 2)

c12 2 (a12)

cij = (-1)i+j M ij
c12 = (-1)1+2 M 12
= (-1) 3 1
0 1
= (-1) [ (3)(1) (0)(1) ]
= (-1)(3-0)
= (-1)(3)
= -3

17
A =

1 3
2 1
0 2
8 12

1
4
-2
16

0
1
1
0

det A 4
det A = a14 C14 + a24C24 + a34 C34 + a44 C44
= 0 C14 + (1)C24 + (1) C34 + 0C44
C24 Cij = (-1)i+j M ij
C24 = (-1)2+4 M 24
1 3 1 1 3
= (1) 0 2 -2 0 2

24

C34

8 12 16 8 12
= (1) [(1) (2)(16) + (3)(-2)(8) + (1)(0)(12) (8)(2)(1) (12(-2)(1) (16)(0)(3)]
= (1) [32 48 + 0 16 + 24 0]
= (1) (-8)
= -8
Cij = (-1)i+j | M ij|
C34 = (-1)3+4 | M 34|

det A

1 3 1 1 3
= (-1) 2 1 4 2 1
8 12 16 8 12
= (-1) [(1) (1)(16) + (3)(4)(8) + (1)(2)(12) (8)(1)(1) (12(4)(1) (16)(2)(3)]
= (-1) [16 96 + 24 8 - 48 96]
= (-1) (-16)
= 16
= (1) (-8) + (1) (16)
=8
1)

2) 0


1) 0 det 0
2) () k (-1)K

3) 2 2 A det A = 0

25
4) A det A = det (At)
5) A nxn det (KA) = Kndet A K
6) B A K
() A |B| = K|A|
7) K

8) A B nxn det(A) det(B) = det(AB)

(Inverse of a matrix)
A B nxn AB = n = BA B
A A B
A A-1 B = A-1

A A-1 = n = A-1A

A =

1 2 3
1 3 5
1 5 12

11
3
7
3
2
3

-3
3
-1

1
3
2
3
1
3

26

A-1

11
3
7
3
2
3

3
-1

1
3
2
3
1
3

A A-1 = n = A-1A

11
3
7
3
2
3

-3

1
3
2
3
1
3

-3
3
-1

5 12

5 12

11
3
7
3
2
3

-3
3
-1

1
3
2
3
1
3


A B nxn
1) (A-1) -1 = A
2) (AB) -1 = B-1A-1
3) (At) -1
= (A-1) t

1)
2)
3)
1)


27
A . A-1 = n = A-1A

A =

2 5
1 3

A-1

A-1 =

x y
w z

A A-1 = n

2
1

5
3

2x + 5w =
2y + 5z =
1x + 3w =
1y + 3z =
(4) x 2 2y + 6z
(2) (5) ;
-z
z

x y
w z

1
0

0
1

1
0
0
1
= 2
= -2
= 2

__________(1)
__________(2)
__________(3)
__________(4)
_____________(5)
( -1 )

(3) x 2 2x + 6w = 0 _____________(6)
(1) (6) ;
-w = 1
w = -1
(1) w = -1
2x + 5(-1) = 1

28
2x = 1 + 5
x =
=
z = 2
2y + 5(2) =
2y =
y =

(2)

x y
w z

3
-1

6
2

3

0
-10
-5
= A-1

-5
2

A - A-1 =

2
1

5
3

3
1

-5
2

1
0

A =

A-1 =

a
c
1
ad bc

b
d
d

-b

-c

A-1 =

2
1

5
3

1
(2)(3) (1)(5)

-5

-1

0
1

29

1
1

-5

-5

-1

-1

2.
3
1) i j A
Ri
Rj
2) i K
KRi
R

, K 0

3) i r i K j
rRi + K Rj
RI , r , K 0
(row equivalent)
A nxn A
[A | n ] [ n | A-1]
[A | n ] [ n | A-1]

1
1
1

2
3
5

3
5
12

1
1
1

2
3
5

3
5
12

1
0
0

0
1
0

0
0
1

1
0

2
1

3
2

1
-1

0
1

0
0

(-1) R1 + R2

30
(-1) R1 + R3

-1

-2 R2 + R1
(-3) R2 + R3

1
0
0

0
1
0

-1
2
3

3
-1
2

-2
1
-3

0
0
1

-1

-2 0

1
R3
3

-1

2
3

-1

1
3

11
3

-3

1
3

-1

-1

1
3
1
3

(-2) R3+ R2 0

2
3
11
3
7

3
2
3

-3

1
3
2

3
1
3

R3+ R1

A-1 =

11
3
7

3
2
3

3
-1

-3
3
-1

2
3
1
3

3. (Adjoint matrix)
A A adj(A)
A-1 =

1
det A

adj (A)

adj (A) = [Cij]t nxn

det A 0
Cij = (-1)i+j Mij

31

1
1
1

A =

A-1

2
3
5

3
5
12

|A|

|A|

= (1)(3)(12) + (2)(5)(1) + (3)(1)(5) - (1) 3(3) (5) 5(1) - (12) (1)(2)


= 36 + 10 + 15 9 - 25 - 24
= 3
1
1
1

2
3
5

3
5
12

1 2
1 3
1 5
+ +

A=

A-1

1
1
1

2
3
5

3
5
12

|A| = (1) 3 (12) + (2) 5 (1) + (3) 1 (5) (1) 3 (3) (5) 5 (1) (12) 1 (2)
= 36 + 10 + 15 9 25 - 24

32

-1

adj
| A|

CoA
A =

C11

= (-1)1+1 M11
= (1) 3 5
5 12
= (1) [(3) (12) (5) (5)]
= 11

C12

= (-1)1+2 M12
= (-1) 1 5
1 12
= (-1) [1(12) 1(5)]
= -7

C13

= (-1)1+3 M13
= (1) 1 3
1 5
= (1) [1 (5) 1(3)]
= 2
= (-1)2+1 M21
= (-1) 2 3
5 12
= (-1) [2 (12) (5) (3)]
= -9

C21

C22

= (-1)2+2 M22
= (1) 1 3
1 12
= (1) [1(12) 1(3)]

| A|

Cij = (-1)i+j Mij

33
= 9
C23

= (-1)2+3 M23
= (-1) 1 2
1 5
= (-1) [1 (5) 1(2)]
= -3

C31

= (-1)3+1 M31
= (1) 2 3
3 5
= (1) [2 (5) 3 (3)]
= 1

C32

= (-1)3+2 M32
= (-1) 1 3
1 5
= (-1) [1(5) 1(3)]
= -2

C33

= (-1)3+3 M33
= (1) 1 2
1 3
= (1) [1 (3) 1(2)]
= 1

A-1

A = CoA

adj
| A|

11

| A|

-7

34
=

CoA

CoAt

-9
1

9
-2

-3
1

11
-7
2

-9
9
-3

1
-2
1

A-1 = CoA =

det A

A-1

A-1 =

11
3
7
3
2
3

9
3
9
3
3
3

1
3
2
3
1
3

11
3
7
3
2
3

9
3
9
3
3
3

1
3
2
3
1
3

11
3
7
3
2
3

-3

1
3
2
3
1
3

3
1

A A-1 =
1

12

11
3
7
3
2
3

-3
3
1

1
3
2
3
1
3

35

(Game Theory) (Linear Programming)
(Solution of Simul taneous linear Equation)
3
1) ( )
2)
3) (Gauss Jordan reduction)
1)


n n

a11 x1 + a12 x2 + . + a1nxn = b1


a21 x1 + a22 x2 + . + a2nxn = b2
.
.
.
.
.
.
an1 x1 + an2 x2 + . + annxn = bn

a11 a12 . a1n
a21 a22 . a2n
.

. . . .
an1 an2 . ann
A

x1
x2
.
.
xn

b1
b2
.
.
bn

36
X
B

Ax = B
A-1
A-1(AX) = A-1B
n X
= A-1B
X
= A-1B

( A-1A = )
( n X = X)

X A A-1 B



2x y + 3z = 1
x+y+z = 4
2x + 4y +4z = -6
AX = B
2 -1
1 1
2 4
X

A-1

3
1
4
= A-1B

x
y
z

1
4
-6

1
4
1
4

1
4
5
4

1
2
1
8
3
8

1
2

11

37

1
4
1
4

x
y
z

=
=
=

1
4
5
4

1
8
3
8

-6

-7

11
0
-7

2)
(Cramers rule)

AX = B

= det A
j
= det (Aj)
= |Aj|
j A j B
xj , xn ,, xn
x1 =

x2 =

, x3 =

x, y, z,
x =
y =
z =

Gramers rule
2x y + 3z = 1
x+y+z = 4
2x + 4y +4z = -6

xn =

38
AX = B

2
1
2

-1
1
4

3
1
4

x
y
z

2 -1
A = 1 1
2 4

=
=
=

=
=
=

3
1 ,X=
4

2
1
2

1
4
-6

-1
1
4

3
1
4

-1
1
4

3
1
4

x
y
z

,y =

1
4
-6

2 -1
1 1
2 4
+
+ +
(2)(1)(4) + (-1)(1)(2) + (3)(1)(4) - (2)(1)(3) - (4)(1)(2) - (4)(1)(-1)
18 2 + 12 6 8 + 4
8
1 -1
4 1
-6 4
+
+ +
(1)(1)(4) + (-1)(1)(-6) + (3)(4)(4) - (-6)(1)(3) - (4)(1)(1) - (4)(4)(-1)
4 + 6 + 48 + 18 4 + 16
88
2 1 3
1
4
-6

39
2

1
2

4
-6

1
4

2
1
2

-1
1
4

1
4
-6

y =

z =

= 0

= -56

88
8

= 11

0
= 0
8
56
=
= -7
8
=

x = 11
y= 0
z = -7

3) (gauss)

[AB]
(Argumented matrix) B]
(Echelon matrix)



2x + 3y = 10
-x + 2y = 3
AX = B

2 3
-1 2
[AB] =

x
y

=
2 3

10
3
10

40

1
R1
2

-1

3
2

-1

R1 + R2

3
2
7
2
3
2

5
8
5

2
16
R2
0 1
A (echelon matrix)
7
7

x y
3
1
5
2
16
0 1
7
3
1x + y = 5 -------------(1)
2
16
0x + 1(y) =
-------------(2)
7
16
(2)
y =
(1)
7
3 16
x +
= 5
2 7
24
x +
= 5
7
24
x = 57
11
=
7

41
2x y + 3z = 1
x+y+z = 4
2x + 4y +4z = -6

[AB]
2 -1 3
1
1 1 1
4
2 4 4
-6

R1 + (-1)R2

1
1
2

-2
1
4

2
1
4

-3
4
-6

1
R3
2

-2

-3

-3

R1 + (-1)R3

0
1
1

-4
1
2

0
1
2

0
4
-3

R1 R2

1
0
0

1
-4
1

1
0
1

4
0
-7

R1 + (-1)R3

1
0
0

0
-4
1

0
0
1

11
0
-7

-4

42
R3 + (-1)R2

1
0

1
1

1
1

4
-7

1
- R2
4

11

-7

R3 + (-1)R2

0
0
0

0
1
0

0
0
1

11
0
-7

x = 11, y = 0 , z = -7

43